Can I prove that these hands are mine? Wittgenstein and Merleau-Ponty on the body - Carrillo, Lucy (Estudios de Filosofía, 2008)
The ancient belief that humans are beings composed of body and soul alleviates the despair that this life is all we have, appeasing the fear of death by offering the illusion of a life without the painful burden of the body; but it also justifies prejudices and superstitions arising from phenomena such as dreams, hallucinations or mere imagination. These deep motivations would receive a powerful justification with Cartesian philosophy. However, accepting that mind and body are two different substances has raised important problems for which there appear to be no satisfactory answers. [Fragment]